A new perspective on market dynamics: Market plasticity and the stability–fluidity dialectics. (September 2014) - Nenonen, Suvi; Kjellberg, Hans; Pels, Jaqueline; Cheung, Lilliemay; Lindeman, Sara; Mele, Cristina; Sajtos, Laszlo; Storbacka, Kaj
Several researchers have pointed out that if marketing is to develop as a discipline and contribute to solving complex business and societal challenges, it should question the neoclassical view of markets and develop its own theory of markets. Efforts in this direction indicate an emerging view of markets as dynamic, subjective, and subject to multiple change efforts. However, the neoclassical view of objective, detached, and deterministic market still influences the dominant models used to describe market change. We argue that in order to better understand market dynamics, both academics and practitioners need new concepts and constructs that go beyond existing linear process and development stage models. We seek to contribute to improved understanding of markets by studying a special characteristic of markets that enables market dynamics. Borrowing a term used by Alderson (1957: 277), we propose that markets are characterized by plasticity, that is, a "potentiality for being remolded and responding in a different way thereafter." Even though the plasticity concept was introduced into the marketing literature nearly 60 years ago, the plastic character of markets remains underresearched. This article investigates the meaning and manifestations of market plasticity, drawing analogies from the physical, natural, and social sciences. We define market plasticity as the market's capacity to take and retain form and propose that the dialectic between market stability and market fluidity lies at the heart of market change.